Analisis Brand Image Hotel Sofyan, Cut Meutia, Jakarta, sebagai Hotel Berkonsep Syariah - Firdaus Suwarta (Destinesia : Jurnal Hospitaliti dan Pariwisata, 2022)
The purpose of this study is to describe of the big line of islamic hotel concept through brand image of hotel Sofyan Cut Meutia Jakarta. This study uses a type of qualitative descriptive. This study uses three kinds of data collection techniques, namely primary data by interview and observation,  and also secondary data. The result of this study shows that Hotel Sofyan Cut Meutia Jakarta already performs a brand image of Syariah Hotel to communicate Islamic concept of its. All of the elemens of brand image have been respresented the whole of facilities and services in Sofyan Hotel Cut Meutia Jakarta so that the public are able to understand the messages have been told.Based on Regulation of Menteri Pariwisata dan Ekonomi Kreatif Republik Indonesia Nomor 2 Tahun 2014 Tentang Pedoman Penyelenggaraan Usaha Hotel Syariah, Hotel Sofyan Cut Meutia is classified as Hotel Syariah Hilal 2.